2013
DOI: 10.1103/physrevlett.111.027404
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Reflective Optics for the Soft Gamma-Ray Photon Energy Range

Abstract: Traditional multilayer reflective optics that have been used in the past for imaging at x-ray photon energies as high as 200 keV are governed by classical wave phenomena. However, their behavior at higher energies is unknown, because of the increasing effect of incoherent scattering and the disagreement between experimental and theoretical optical properties of materials in the hard x-ray and gamma-ray regimes. Here, we demonstrate that multilayer reflective optics can operate efficiently and according to clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…With a range of multilayer periods present, Bragg's law is fulfilled at additional angles of incidence thereby broadening the response. The feature did not present itself in previous X-ray campaigns at lower photon energies, on account of the relatively small beam footprints (10 mm, [20]) along the direction of the beam. The reduced grazing incidence angle and increased beam vertical size in use above 0.5 MeV results in an order of magnitude longer footprint.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…With a range of multilayer periods present, Bragg's law is fulfilled at additional angles of incidence thereby broadening the response. The feature did not present itself in previous X-ray campaigns at lower photon energies, on account of the relatively small beam footprints (10 mm, [20]) along the direction of the beam. The reduced grazing incidence angle and increased beam vertical size in use above 0.5 MeV results in an order of magnitude longer footprint.…”
Section: Resultsmentioning
confidence: 92%
“…Recent research has shown that multilayer coatings can reflect X-rays efficiently at 0.38 MeV [20] where incoherent scattering effects become non-negligible. With the present work, we have nearly doubled the proven range of operation to 0.65 MeV an improvement that may enable new applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Details of this work have been published in 2013 in two refereed papers [20,21] and are briefly summarized below.…”
Section: Development Of Gamma-ray Mirrorsmentioning
confidence: 99%
“…Another solution to concentrate hard X-rays consists of multilayer optics, which was recently proved to focus photons of up to hundreds of keV with high-efficiency and according to classical-wave physics [3,4]. However, these new reflective optics work at very low grazing incidence angles, below 0.1 • , thus featuring a very low acceptance area for the incident photons.…”
mentioning
confidence: 99%
“…The legend describes the diffracting plane employed. The crystals are 10×30×5 mm3 Si and Ge tiles. The disposition of the tiles is optimized with a specifically written code, named LaueGen…”
mentioning
confidence: 99%